Relação de idosos com a linguagem e com a velhice em um grupo dialógico-operativo - Lourenço, Regina Célia Celebrone (2014)
In an aging Brazil, where the elderly population will be the majority in the coming decades, it urges the creation of resolutions that answer the subjective aspects of aging, the uncouple the senses as impotence and exclusion. The Language Workshop group, that gathers weekly in Curitiba to read, tell and write life stories, emerges in this scenario, as an initiative to make changes in the elderly relationship with their processes of aging methods and language. This assessment aims to analyze the effects that the dialogic activities in the operating group of Language Workshop, practiced in respect of elderly with language and with aging after socio- discursive interactions that focus on the writing and publishing an autobiographical narrative at the end of each year group activities. This is a qualitative study, and the development of activities was guided by the philosophy of language Mikhail Bakhtin, and the data analyzed by the assumptions operative group Pichon-Rivière and the Bakhtinian dialogism. Furthermore, for data collection, a semi-structured interview was applied along the thirteen seniors who composed the dialogical – operative group, added to notes made in the field diary during the Workshop meetings by the researcher. These statements announce that group practices permeated by socioverbal activities in operative groups, make changes in the relations of elderly participants with their own ways of relating with other people, be it family, group of friends, or the social environment in which they operate. The Dialogical interactions provided them self-esteem, personal safety, place of authorship that push them to spell out their speeches in the most heterogeneous social scenes. Thus, the research presents the dialogical speech-operative Group as opportunity of developing practices with language, indicating that socio-verbal activities based on a solid dialogical perspective, can be configured as a capable alternative of making significant aging methods and endowed with the meaning in the Brazilian aging society.